Effects of MiR‐137 genetic risk score on brain volume and cortical measures in patients with schizophrenia and controls. Issue 3 (8th February 2018) - Cosgrove, Donna; Mothersill, David O.; Whitton, Laura; Harold, Denise; Kelly, Sinead; Holleran, Laurena; Holland, Jessica; Anney, Richard; Richards, Alex; Mantripragada, Kiran; Owen, Michael; et al.
Abstract : Multiple genome‐wide association studies of schizophrenia have implicated genetic variants within the gene encoding microRNA‐137. As risk variants within or regulated by MIR137 have been implicated in memory performance, we investigated the additive effects of schizophrenia‐associated risk variants in genes empirically regulated by MIR137 on brain regions associated with memory function. A polygenic risk score (PRS) was calculated (at a p = 0.05 threshold), using this empirically regulated MIR137 gene set, to investigate associations between this PRS and structural brain measures. These measures included total brain volume, cortical thickness, cortical surface area, and hippocampal volume, in a sample of 216 individuals consisting of healthy participants ( n = 171) and patients with psychosis ( n = 45). We did not observe a significant association between MIR137 PRS and these cortical thickness, surface area or hippocampal volume measures linked to memory function; a significant association between increasing PRS and decreasing total brain volume, independent of diagnosis status ( R 2 = 0.008, Beta = −0.09, p = 0.029), was observed. This did not survive correction for multiple testing. In conclusion, our study yielded only suggestive evidence that risk variants interacting with MIR137 impacts on cortical structure.